PENGARUH PENGGUNAAN MASKER BENGKUANG TERHADAP PEMUDARAN NODA BEKAS JERAWAT - Noveta, Rahyu; Rahmiati, Rahmiati; Astuti, Murni (Journal of Home Economics and Tourism, 2014)
This study aimed to analyze the effect of using pachyrizus masks against acne scars fading stains judged from the brightness level of skin color and fading acne scars blemishes. Acne scarsoften complained, especiallyadolescentsaged18-25yearsyoung adultsorinpuberty. The study was conducted with three different treatment groups , namely control group (X0) , experimental group 1 (X1) and experimental group 2 (X2) . Designresearchis was Quasi Experiment with Nonequivalent Control Group . The object of research is a stain on the skin of acne scars . The sampling technique used purposive sampling conducted in volunteers . Data collected in the form of primary data collected directly from the sample by filling out the assessment form has been provided . Analysis of the data using Analysis of Variance and Duncan test . The research indicate that acne scars fading stains without the use of pachyrizus mask on X0 group showed no significant change in the results towards better on every indicator , for X1 group showed significant gains in each indicator as well as the X2 group showed a significant result on each indicator. The use of masks pachyrizus stains can fade acne scars and brighten the skin with the regular use by the usage frequency of 1 times in 3 days treatment group X1. Â  Kata Kunci : masker bengkuang, noda bekas jerawat